2018
DOI: 10.1002/ece3.4781
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator‐mediated interactions between cultivated papaya and co‐flowering plant species

Abstract: Many modern crop varieties rely on animal pollination to set fruit and seeds. Intensive crop plantations usually do not provide suitable habitats for pollinators so crop yield may depend on the surrounding vegetation to maintain pollination services. However, little is known about the effect of pollinator‐mediated interactions among co‐flowering plants on crop yield or the underlying mechanisms. Plant reproductive success is complex, involving several pre‐ and post‐pollination events; however, the current lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
0
4
0
2
Order By: Relevance
“…It was also greater than that observed in cultivars of Mexico, since it exceeded that reported by Burquez and Sarukhán (1980) in the state of Morelos (five species reported, including hummingbirds for the first time) and by Sousa-Peña (1992) in Chihuahua, where 16 species of visitors were found, including hummingbirds. The greater number of floral visitors found in our studies could be attributed to the combination of flowers present in the fields, as well as to the diversity of co-flowering species around the fields (Badillo-Montaño et al, 2018). It could also partly be due to the fact that the study was developed in a locality belonging to a region (the states of Puebla, Oaxaca and Chiapas) in which a high diversity of wild and domesticated forms of P. coccineus is concentrated (Delgado Salinas, 1988).…”
Section: Discussionmentioning
confidence: 56%
“…It was also greater than that observed in cultivars of Mexico, since it exceeded that reported by Burquez and Sarukhán (1980) in the state of Morelos (five species reported, including hummingbirds for the first time) and by Sousa-Peña (1992) in Chihuahua, where 16 species of visitors were found, including hummingbirds. The greater number of floral visitors found in our studies could be attributed to the combination of flowers present in the fields, as well as to the diversity of co-flowering species around the fields (Badillo-Montaño et al, 2018). It could also partly be due to the fact that the study was developed in a locality belonging to a region (the states of Puebla, Oaxaca and Chiapas) in which a high diversity of wild and domesticated forms of P. coccineus is concentrated (Delgado Salinas, 1988).…”
Section: Discussionmentioning
confidence: 56%
“…For domesticated papaya, Badillo‐Montaño et al . (2019) studied whether three varieties of papaya (Maradol, Msxj and BS‐2) shared pollinators with the co‐flowering plants in an experimental plantation in Muna, Yucatan. They found that the cultivated varieties shared at least one pollinator species with 88% of the co‐flowering plant species in their study area, including wild papaya plants.…”
Section: Discussionmentioning
confidence: 99%
“…La interacción planta-abeja, sin duda forma parte de una historia coevolutiva importante, como mencionan Bloch et al (2017), las plantas han desarrollado algunas características para facilitar la polinización por las abejas como son: el color, el aroma y la apertura de las flores, así como la producción de recompensas para los polinizadores, tales como néctar, polen y resinas. Estas interacciones entre plantas y abejas sin aguijón contribuyen en la polinización de los agroecosistemas (Kevan y Silva, 2020), lo cual se torna importante debido a que entre 75 y 84% de las especies cultivadas dependen de la polinización para la producción de frutos y semillas (Meléndez et al, 2018;Badillo-Montaño et al, 2019). (Friese, 1900), utilizan materiales antropogénicos como material de anidación (Vieira et al, 2016).…”
Section: Las Abejas Sin Aguijón Y La Polinizaciónunclassified